Relation of Epidermal Growth Factor Receptor Expression to Mucus Hypersecretion in Diffuse Panbronchiolitis - Kim, Je-Hyeong; Jung, Ki-Hwan; Han, Joung-Ho; Shim, Jae-Jeong; In, Kwang-Ho; Kang, Kyung-Ho; Yoo, Se-Hwa (Chest, 2004)
Study object: Diffuse panbronchiolitis (DPB) is a hypersecretory airway disease, and the mechanism of mucus hypersecretion in DPB is poorly understood. Moreover, mucin synthesis in the airways has been reported to be regulated by neutrophilic inflammation-induced epidermal growth factor receptor (EGFR) expression, and the degranulation of goblet cells is known to be mediated by neutrophilic elastase. In this study, we examined the relationship between EGFR expression in the bronchiolar epithelium with neutrophilic inflammation and mucus hypersecretion in the tissues of DPB patients. Design: The tissue specimens of 13 DPB patients and 6 healthy control subjects were examined by alcian blue/periodic acid-Schiff (AB/PAS) staining for mucous glycoconjugates, and by immunohistochemical staining for MUC5AC, EGFR, tumor necrosis factor-Î±, and CD16 on neutrophils. Results: Neutrophilic inflammation was significantly higher in the tissue of DPB patients than in that of control subjects (p = 0.002). In the bronchiolar epithelium, goblet cell metaplasia, by AB/PAS staining and mucin MUC5AC expression, was significantly higher than that in control subjects (p = 0.001 and p = 0.002, respectively). In addition, the morphometric quantification of intraluminal mucus secretion showed that the areas of the bronchiolar lumen occupied by mucus secretion were significantly increased in the tissue of DPB patients (p = 0.001), suggesting goblet cell degranulation. EGFR expression was observed in the bronchiolar epithelium of DPB patients, but not in that of control subjects. Conclusions: In DPB, we suggest that mucus hypersecretion due to goblet cell metaplasia is closely associated with neutrophilic inflammation and the expression of EGFR. The study also shows that intraluminal secretion due to the degranulation of goblet cells degranulation is related to neutrophilic inflammation.